Segmentation of current and potential investors in retirement plans to retain and capture customers - Ronaldo Andrade Deccax; Carlos Heitor Campani (BBR: Brazilian Business Review)
The goal of this research was to fill the gap represented by the lack of studies that apply Behavioral Finance concepts in the segmentation of investors in retirement savings plans. Based on a bibliographic review, and the study of multiple cases, there was revealed relevant aspects of the supplemental retirement market in Brazil, this article proposes a new set of demographic and psychographic variables that were more effective in previous research in the segmentation of financial services clients. It innovates by incorporating variables from Psychology and Behavioral Finance, especially the “rationality” variable which has a remarkable ability to synthesize vulnerabilities to a wide universe of heuristics and biases when applied to investors. In addition, significant behavioral barriers were identified for the expansion of the retirement market, such as a low level of maturity of current market practices in Brazil and the need to use Behavioral Finance instruments in this confrontation.